Facile Synthesis of Magnetic Nigella Sativa Seeds: Advances on Nano-Formulation Approaches for Delivering Antioxidants and Their Antifungal Activity against Candida albicans - Maqsood Ahmad Malik; Laila AlHarbi; Arshid Nabi; Khalid Ahmed Alzahrani; Katabathini Narasimharao; Majid Rasool Kamli (MDPI AG, 2023)
This article reports on incorporating magnetic nanoparticles into natural carbon frameworks derived from Nigella Sativa seeds and their synthesis via co-precipitation reactions for application in biomedicine. The magnetic Nigella Sativa Seeds (Magnetic NSS), a metal oxide-based bio-nanomaterial, has shown excellent water diaper presence due to the presence of a wide range of oxygenous hydroxyl and carboxyl groups. The physicochemical properties of the composites were characterized extensively using Fourier transform infrared spectroscopy (FTIR), powder-X-ray diffraction (XRD), scanning electron microscopy (SEM), elemental analysis, transmission electron microscopy (TEM), and vibrating-sample magnetometer. Furthermore, synthesized magnetic NSS showed antioxidant and antifungal activity. The antifungal susceptibility was further tested against Candida albicans with a MIC value of 3.125 µg/mL. Analysis of antioxidant defense enzymes was determined quantitatively; the results suggested that antioxidant enzyme activity increase with increased magnetic NSS concentration. Furthermore, biofilm inhibition assay from scanning electron microscopy results revealed that magnetic NSS at the concentration of 3.5 μg/mL has anti-biofilm properties and can disrupt membrane integrity.